Risk Management Design in Startup Company PT. Financial Statement Assistant - Tantri Yanuar Rahmat Syah; Edi Hamdi; Agus Munandar; Simon Petrus Hendrik Hutapea (Syntax Corporation Indonesia, 2023)
Rapid technological development encourages Indonesia's economic growth. The background of this study is the ignorance of start-up companies about the existence of business risks and bankruptcy failures. The purpose of this study is to develop risk management plans and guidelines according to ISO 31000: 2018 The company strives to support business progress by recruiting qualified workers in their fields to be responsible for technological innovation and security of the company's database. Risk management can be applied to minimize the risk of business processes to achieve business objectives